2022
DOI: 10.2196/33361
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perceptions of Dermatologic Photography: Scoping Review

Abstract: Background Medical photography is used extensively in dermatology to record disease progression, measure treatment response, and help teach patients about skin disease; such photos are also commonly utilized in teledermatology, medical education, research, and medical reference websites. Understanding patient perceptions of medical photographs obtained during dermatologic care in the clinic or hospital setting is critical to enable the delivery of high-quality, patient-centered medical care. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…With store-and-forward platforms, good photography forms the basis of the consult—where clinical photos inform on the evolution of a skin disease and assist in more objective assessments of a patient when different doctors are involved in patient care such as in larger public hospitals [ 5 ]. A scoping review by Kim and Sivesind [ 7 ] had also demonstrated that patients adopt positive attitudes toward medical photography. Most patients had expressed that medical care could be improved in the clinical setting with photography [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…With store-and-forward platforms, good photography forms the basis of the consult—where clinical photos inform on the evolution of a skin disease and assist in more objective assessments of a patient when different doctors are involved in patient care such as in larger public hospitals [ 5 ]. A scoping review by Kim and Sivesind [ 7 ] had also demonstrated that patients adopt positive attitudes toward medical photography. Most patients had expressed that medical care could be improved in the clinical setting with photography [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…A scoping review by Kim and Sivesind [ 7 ] had also demonstrated that patients adopt positive attitudes toward medical photography. Most patients had expressed that medical care could be improved in the clinical setting with photography [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason, clinicians should obtain proper patient consent, explain how images will be used, and delete the images from their smartphones after being uploaded to patient charts while ensuring sufficient security in their digital communications [ 50 ]. In general, patients prefer giving verbal consent and their photographs being taken by clinic- or hospital-owned cameras [ 51 ]. EHR programs such as Epic and Cerner as well as new mobile apps allow for the secure upload of patient images to their medical charts without permanent storage on the user’s device [ 52 ].…”
Section: Discussionmentioning
confidence: 99%